(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2016)
This study took place in three rooms in one building, give and take the external conditions were relatively similar. The study aims to observe the level of acoustic comfort and suggest strategies to improve the acoustic comfort by modifying materials and dimensions of the materials. The modification is much needed in practice since the user critize the acoustical comfort of the room. The method applied was simply measuring the condition of the rooms using laser distance meter and sound level meter, taking notes on the characteristic of the material used, and developing simulation based on several modifications in materials and dimensions of the materials. The result of the simulation was then being compared to the standart of reverberation time. The conclusion of the study was made into three points: (1) the acoustic condition in the rooms are indeed not meeting the standart to ensure users’ comfort, (2) the reverberation time is better when additional plasterboard ceiling are built, thus changing the rooms’ dimension; and (3) the noise in each room is not significantly reduced even after the additional ceiling built. The simulation in this study was done through the help of Ecotect 2011.